1991
DOI: 10.1002/ajmg.1320380424
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological aspects of Mendelian syndromes in a spanish population sample: I. Autosomal dominant malformation syndromes

Abstract: Using a sample of 710,815 liveborn infants throughout Spain, monitored from April, 1976, to December, 1988, by the Spanish Collaborative Study of Congenital Malformations (ECEMC), we estimated the prevalence of each recognized autosomal dominant malformation syndrome for a total prevalence figure of 12.1 per 100,000 live births, including all detected autosomal dominant malformations syndromes. We estimated that the mutation rate for those syndromes was 48.5 per 1,000,000 gametes. The geographical distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 10 publications
4
9
0
Order By: Relevance
“…This study showed that the incidence of birth defects at birth is 31.46/1000 total birth. This rate is higher than that found in many developed as well as some developing countries, while it appears similar to that observed in some neighboring countries (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) (Table 3). However the expected rate in our study could be higher as some of the congenital malformations might not be evident at birth like cardiovascular, internal gastrointestinal tract, and renal anomalies.…”
Section: Discussionsupporting
confidence: 81%
“…This study showed that the incidence of birth defects at birth is 31.46/1000 total birth. This rate is higher than that found in many developed as well as some developing countries, while it appears similar to that observed in some neighboring countries (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) (Table 3). However the expected rate in our study could be higher as some of the congenital malformations might not be evident at birth like cardiovascular, internal gastrointestinal tract, and renal anomalies.…”
Section: Discussionsupporting
confidence: 81%
“…13,14 It is still higher than that reported by the WHO in other populations (12.7 per 1000) in 16 countries. 13 Other studies among live born neonates showed different prevalence figures; in Spain (20.23 per 1000), 15 in Libyan Arab Jamahiriya (23.8 per 1000), 16 in India (27.2 per 1000), 17 and the Federal Republic of Germany where figures of 6.9% for major malformation and 35.8% for mild errors of morphogenesis were reported among live births, stillbirths and abortions. 18 …”
Section: Discussionmentioning
confidence: 97%
“…The group of short‐limb skeletal dysplasias includes several clinically distinct syndromes, the most studied being achondroplasia (ACH), TD types I (TDI) and II (TDII), hypochondroplasia (HCH), and, to a lesser degree, severe achondroplasia with developmental delay and acanthosis nigricans (SADDAN). These are among the most frequent congenital defect syndromes detected at birth [Martínez‐Frías et al, 1991; Bermejo et al, 2005].…”
Section: Summary Of Some Epidemiological Clinical and Genetic Issuesmentioning
confidence: 99%